C.1 - Seyid Muhammed, V. A. (Delhi, 1975)
In his book Mr. Palkhivala has very impressively marshalled quotations from Plato to Pascal, from Lord Acton to Maurice Chevalier. Generally speaking, facts and arguments should be strong enough to stand by themselves without having to resort to the crutches of lengthy quotations. His quotations are impressive and profound. Nobody need quarrel with them. But what one differs from is the fact that many of those are used out of context and the inferences and reasoning which are derived from them are not always justified.
Keywords: India-Constitution